2020
DOI: 10.5222/terh.2020.15045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health Beliefs and Knowledge Status of Nursing Students Related to Osteoporosis

Abstract: Sınıf düzeyi ile öğrencilerin bilgi testi ve sağlık inanç toplam puanı arasında istatistiksel olarak anlamlı bir fark saptanmıştır (p<0,001). Sonuç: Öğrencilerin osteoporoz bilgi ve sağlık inancı puanlarının orta düzeyde olduğu ve eğitim seviyesinden etkilendiği tespit edilmiştir. Osteoporoz bilgisi ve sağlık inancını arttırıcı, yaşam tarzı değişikliklerini içerecek eğitici yaklaşımlarda bulunulmalıdır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Osteoporosis, which affects bone mineral density and quality, is an important public health problem that causes increasing disability, death and economic losses and affects a large part of society (Acıkgoz et al, 2020; Kalkim & Dağhan, 2017). According to the data of the International Osteoporosis Foundation (IOF), 200 million people are affected by osteoporosis globally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis, which affects bone mineral density and quality, is an important public health problem that causes increasing disability, death and economic losses and affects a large part of society (Acıkgoz et al, 2020; Kalkim & Dağhan, 2017). According to the data of the International Osteoporosis Foundation (IOF), 200 million people are affected by osteoporosis globally.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are studies on health education given to women in the postmenopausal period by nurses based on the HBM. In these studies, positive improvements were reported in the rate of women's calcium intake, exercise behaviours, self‐efficacy and health beliefs (Acıkgoz et al, 2020; Kalkim & Dağhan, 2017). The components of HBM are perceived susceptibility, perceived severity, perceived benefits, perceived barriers, health motivation, and self‐efficacy (Acıkgoz et al, 2020; Jeihooni et al, 2016; Nguyen, 2016).…”
Section: Introductionmentioning
confidence: 99%